A rare case in an adolescent patient with nasal polyps resistant to polypectomy: Samter’s syndrome (Annals of Medical Research, 2021)
The comorbidity of recurrent nasal polyps, non-steroidal anti-inflammatory drug hypersensitivity and chronic rhinosinusitisis called Samter’s syndrome. It is less common in childhood than in adulthood. Patients first have nasal symptoms and thenasthma and non-steroidal anti-inflammatory drug (NSAID) hypersensitivity begin to accompany. For definitive diagnosis, NSAIDor aspirin hypersensitivity must be shown with provocation test. In this case report, oral provocation test with ibuprofen wasperformed on a 17-year-old female patient who had recurrent nasal polyps and chronic rhinosinusitis accompanied by asthmaand NSAID hypersensitivity and the test was found to be positive. The patient was diagnosed with Samter’s syndrome and aspirindesensitization was applied. Inhaled steroid, intranasal steroid and montelukast therapies were started. As a conclusion, althoughit is more common in adults, Samter’s syndrome should also be considered in pediatric patients with recurrent nasal polyp, chronicrhinosinusitis, asthma, and NSAID hypersensitivity.